Efforts to Increase the Success of Islamic Religious Education Learning - Raudlatul Jannah (Universitas Muhammadiyah Sidoarjo, 2017)
Islamic Religious Education in School / Madrasah aims to grow and improve faith through the giving and fertilizing of knowledge, appreciation, understanding and practice of the students about Islam to become a growing Muslim in terms of faith, piety, nation and state. Teachers are one of the factors that influence the success of education. The quality of learning in accordance with the signs of Islamic Education is also influenced by the attitude of creative teachers to choose and implement various approaches and learning models. For the sake of the realization of Islamic Religious Education in accordance with instructional objectives it is necessary to make efforts made continuity in planning, implementation until evaluation. One of the efforts to improve the success of PAI learning such as developing teacher professionalism, improving the success of classroom management, creating a religious atmosphere in the School.